Unfair Access to Justice for Non-Indonesian Speakers - Eni Candra Tampubolon (Faculty of Law, Maranatha Christian University, 2024)
Legal interpreter assistance has a direct impact on the outcomes of legal cases. This paper examines the availability of legal interpreters in Bali as one of the two provinces in Indonesia with the highest demand for legal interpreters and its impact on non-Indonesian speakers. This paper adopts a qualitative research method and draws data from collaborative research conducted between RMIT University and the University of Warmadewa, Bali. It draws data from legal practitioners in Bali with experience working with interpreters. The data was obtained through interviews using semi-structured questions in Indonesian. Subsequently, the responses were translated into English, and the emerging themes were analysed using both inductive and deductive processes. Data collected reveals a concerning shortage of legal interpreters in Bali and a notable disparity between the availability of English-speaking interpreters versus non-English languages. It also exposes the practice of using English-Indonesian language pair interpreters for non-English-speaking individuals due to the unavailability of interpreters in certain languages. This practice negatively impacts fair access to justice in Bali and at the same time increases the potential for future appeals